Problem-Based Learning sebagai Strategi Penguatan Berpikir Kritis dalam Pembelajaran Pendidikan Agama Islam - Fazrin, Intan Solihat; Azizah, Aulia Rahma; Jesinca Aliyyah; Aini, Isna Nurul; Usep Suherman (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2025)
Although Problem-Based Learning (PBL) has been proven effective in improving critical thinking and problem-solving skills, its application in Islamic Religious Education (IRE) at the senior high school level has rarely been studied. IRE learning tends to be passive and theoretical. As a result, students are unable to relate religious values to real-life issues, making learning less contextual and transformative. This study aims to explore in depth the application of Problem-Based Learning (PBL) in building conceptual understanding and developing critical thinking skills of students in Islamic Religious Education (IRE) at SMA Negeri 1 Leles, Garut. Through a case study approach, data was collected through semi-structured interviews, classroom observations, and document analysis, involving PAI teachers, the school principal, and students as key participants. The results of the study indicate that the implementation of PBL enhances students' active participation, encourages critical discussion, and connects learning materials with current issues. Teachers reported an improved collaborative and dynamic classroom atmosphere, while students acknowledged gaining a deeper understanding of Islamic values. This study highlights the potential of PBL as a pedagogical approach aligned with the objectives of PAI, namely fostering reflective thinking and building a moral foundation. However, successful implementation of PBL requires institutional support, professional training for teachers, and availability of resources. This study provides initial insights and opens opportunities for further large-scale and longitudinal research.